Comparison of three targeted approaches to screening for abdominal aortic aneurysm based on cardiovascular risk. Issue 9 (18th July 2016) - Jones, G T; Hill, B G; Curtis, N; Kabir, T D; Wong, L E; Tilyard, M W; Williams, M J A; van Rij, A M
Abstract: Background: Abdominal aortic aneurysm (AAA) continues to be a significant health burden yet few countries have implemented a comprehensive screening programme. Screening typically places emphasis on men aged over 65 years; however, there is concern that other at-risk groups may be underidentified. The present study examined three potential screening strategies based on cardiovascular risk. Methods: The prevalence of AAA was determined by abdominal ultrasound imaging in over 50-year-olds of either sex undergoing coronary angiography, vascular laboratory assessment of peripheral arterial disease, or community-based cardiovascular disease (CVD) event risk assessment. A fourth group, consisting of volunteers aged over 60 years who had no symptoms or signs of cardiovascular disease, was used as a comparator group. Results: A total AAA prevalence of 4·4 per cent was detected across all three strategies (137 of 3142 individuals), compared with 1·0 per cent in the CVD-free group. Male sex, age and smoking were all associated with greater AAA prevalence. Although AAA prevalence was lowest using the community-based strategy, those with an AAA detected were on average 7 years younger than those with AAAs detected with the other two strategies ( P < 0·001). Conclusion: Different strategies, based on CVD risk, resulted in AAA prevalence rates that were significantly greater than that in CVD-free individuals. This may provide opportunities for a targeted approach to community AAA screening in parts of the world where more sophisticated national screening programmes do not exist. Abstract : Supports a targeted approach